Maximum Cervical Dilation Achieved Prior to Uterine Rupture [38A]. (May 2018) - Nitzsche, Brad; King, Victor; Zavala, Kathryn; Wallace, Erika; Reyes, Natalie; Elkattah, Rayan
Abstract : INTRODUCTION: Uterine rupture is a catastrophic obstetrical event with high rates of maternal and fetal morbidity and mortality. Uterine rupture occurs most commonly in patients with prior uterine scars, especially those undergoing a trial of labor after cesarean section. It is intuitive that uterine rupture is more likely to occur in the active stage of labor or at advanced cervical dilation, but data on this subject is lacking. METHODS: All cases of uterine rupture that occurred at a single institution from 2010-2016 were identified using ICD codes. Inclusion criteria were pregnant women age 18 and greater with a history of a prior low transverse uterine incision who underwent a uterine rupture while in labor. The primary endpoint was the maximum cervical dilation achieved prior to the diagnosis of uterine rupture. RESULTS: 19 cases were initially identified, but five of these did not meet inclusion criteria. In the remaining 14 cases, the maximum cervical dilation ranged from 0 to 10 cm with a mean of 3.1 cm. In 9 of the 14 cases, uterine rupture occurred at 4 cm dilation or less. CONCLUSION: Uterine rupture does not appear to be more likely to occur in active than in latent labor.